A study of the Romanian framework and the challenges in implementing the noise mapping legislation - POPESCU, Diana Ioana (Archives of Acoustics, 2023)
The Environmental Noise Directive (END), published in 2002, was transposed into Romanian local law in 2005, and it was the starting point for the first urban noise mapping exercises, initially conducted in nine Romanian cities. This paper presents the main evolutionary aspects of the noise assessment process, the development of strategic noise maps, and action plans, dealing with both the legislative side and the practical approach and results obtained. The study considers the specific regulations established by the European Commission regarding environmental noise assessment and deals with the global context at the country level, in which they have been implemented and applied.